2008
DOI: 10.1021/ic701756p
|View full text |Cite
|
Sign up to set email alerts
|

New Fe4, Fe6, and Fe8Clusters of Iron(III) from the Use of 2-Pyridyl Alcohols: Structural, Magnetic, and Computational Characterization

Abstract: The syntheses, crystal structures, magnetochemical characterization, and theoretical calculations are reported for three new iron clusters [Fe 6O 2(NO3) 4(hmp) 8(H 2O) 2](NO3)2 (1), [Fe4(N3)6(hmp)6] (2), and [Fe8O3(OMe)(pdm)4(pdmH) 4(MeOH)2](ClO4)5 (3) (hmpH=2-(hydroxymethyl)pyridine; pdmH2=2,6-pyridinedimethanol). The reaction of hmpH with iron(III) sources such as Fe(NO3) 3.9H2O in the presence of NEt 3 gave 1, whereas 2 was obtained from a similar reaction by adding an excess of NaN3. Complex 3 was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 122 publications
(96 reference statements)
2
25
0
Order By: Relevance
“…The spin densities have magnitudes close to the formal value of five expected for high spin (d 5 ) Fe 3+ ions but are reduced below this number by spin delocalization, as found with ZILSH for other complexes of Fe 3+ ions. 22,26,30,54 The signs of the local spin densities indicate the relative directions of the spin moments of the iron ions and show that the correct spin distributions were obtained for all the spin components.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The spin densities have magnitudes close to the formal value of five expected for high spin (d 5 ) Fe 3+ ions but are reduced below this number by spin delocalization, as found with ZILSH for other complexes of Fe 3+ ions. 22,26,30,54 The signs of the local spin densities indicate the relative directions of the spin moments of the iron ions and show that the correct spin distributions were obtained for all the spin components.…”
Section: Resultsmentioning
confidence: 93%
“…Calcd for 1a · 2MeCN: C, 28. 54;H,5.23;N,1.51%. Found: C,28.43;H,5.27 6 (H 2 O) 3 ](NO 3 ) (1.03 g, 1.0 mmol).…”
Section: Methodsmentioning
confidence: 98%
“…These have been referred to as (a) planar, (b) twisted-boat, (c) chairlike, (d) parallel triangles, (e) octahedral, (f) fused or extended butterflies, (g) cyclic, and (h) linked-triangles. 29 Such a structural variety has led to many ground-state spin values being determined. Two of these previous Fe 6 complexes, [Fe 6 O 2 (OH) 2 (O 2 CPh) 9 (hep) 4 ] and [Fe 6 O 2 (OH) 2 (O 2 CPh) 10 (hep) 2 ] (hep − is the anion of 2-(2-hydroxyethyl)pyridine), have a core related to 2 and have been obtained with either cis or trans disposition of the monatomic oxo bridges; 9 the core of the latter is trans and has an S = 5 spin ground state, suggesting a possibly similar ground state for 2 (vide infra).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This was also found to be the case with the complex [Fe 8 O 2 (OH) 12 (tacn) 6 ] 8+ (ref 32) but not for the complex [Fe 14 O 6 (bta) 6 (OMe) 18 Cl 6 ], in which DFT calculations gave the correct ground-state spin while ZILSH calculations did not. 68 Clearly comparisons for additional complexes are needed to clarify if one method is consistently more reliable than the other for estimating exchange constants in polynuclear transition metal complexes.…”
Section: B Comparisons Between Methods and Experiments (Fcs Calculatimentioning
confidence: 99%
“…It is also very important to note that in other cases we have observed that the larger exchange constants found with spin couplings obtained from the local spin operator are more consistent with experiment. 33,68 Further study from both theoretical and practical perspectives is needed to clarify these issues.…”
Section: B Comparisons Between Methods and Experiments (Fcs Calculatimentioning
confidence: 99%